Sustainable ceiling panels: exploring the potentials of groundnut shell and sugarcane bagasse-modified plaster of Paris - Ubong Williams Robert; Sunday Edet Etuk; Okechukwu Ebuka Agbasi; David Adeniran Oyegoke; Sylvester Andrew Ekong (Discover Materials)
Abstract Plaster of Paris (POP) ceiling has several advantages over other panels but because it is very expensive, only those in the elite class could afford it. Also, groundnut shell (GNS) and sugarcane bagasse (SGB) are recyclable wastes generated in large quantities annually, yet, majorly under-utilized. The persistence of limited/ ineffective waste management systems in less-developed and developing nations warrants adoption of open burning as their prevalent disposal technique. These situations hinder the achievement of sustainable development. Therefore, this research aimed at exploring the potentials of the GNS and SGB in development of sustainable ceiling panels with POP through appraisal of acoustical insulation, heat transfer, and strength properties of the resulting composite panels. Separate samples were prepared by partially replacing the POP with up to 12.3% weight proportions each of the GNS and SGB. The samples were dried, and then characterized/appraised for acoustical insulation, heat transfer, and strength. It was found that SGB-modified POP samples could improve thermal insulation better than those similarly produced with the GNS. With the GNS and SGB contents, the samples were effective by 99.38% and 99.32%, respectively, in maintaining their outlook during their actual service life. The least strength against bending stress was (2.506 ± 0.002) N/mm2 with the GNS content and (2.376 ± 0.002) N/mm2 for using the SGB in the POP matrix, both of which exceeded the minimum requirement for gypsum ceilings (Code H). Further, it was observed that the samples could provide a desirable level of acoustical comfort ceilings in buildings. The undertaking described in this research can avail the building industry with eco-friendly POP-based ceilings that are capable of mitigating the effects of climate change. Focus on influence of fiber treatment and particle sizes is necessary for future research on the fiber- modified POP ceilings.